Synthesis and Spectroscopic Identification Of A New Series Of Biologically Active 2-Iminothiazolidine-4-One Derivatives - Azeez, Hashim J.; Abdulla, Venos S. (Science Journal of University of Zakho, 2014)
A series of 2-amino-5-(substituted phenyl) 1,3,4- thiadiazol have been synthesized through the reaction of thiosemicarbazide with substituted benzoic acids in the presence of phosphoroxy chloride readily undergo nucleophilic addition – elimination reaction with chloroacetyl chloride in benzene as a solvent to afford 2-chloro acetamido compounds. The prepared compounds were subjected cyclization reaction and results in the formation of a series of 2- imino-3-(substituted phenyl) 1,3,4- thiadiazol-2yl-thiazolidinone -4 one . The IR ,1H and 13C- NMR spectra of the prepared compounds were confirmed to their proposed structures . Finally antimicrobial activity of the newly obtained compounds were tested against Klepsilla pneumonia (gram -ve ) and Staphylococcusaurous (gram + ve) and the results showed that most of the prepared compounds are sensitive against both types of test organisms in different activities .